Assessment of Genetic Distance Among Some Iraqi Date Palm Cultivares )Phoenix Dactylifera L.) Using Randomly Amplified Polymorphic DNA - S. Alansari, Mohammed; Kareem A. Al-kazaz, Abdul; S. Khierallah, Hussam (Iraqi Journal of Science, 2023)
The aim of this study to determine the genetic distance and relationship among some Iraqi date palm cultivars by using the Random Amplified Polymorphic DNA (RAPD) technique. Molecular analysis was performed by using 10 random primers. These primers produced 176 fragment lines across 14 cultivars, Of these, 166 or 94.3% were polymorphic. The size of the amplified bands ranged between 200-2250 bp. The genetic polymorphism value of each primer was determined and ranged between 7.5-16.9%. In terms of unique banding patterns, the most characteristic banding pattern was for the Barhee cultivar with primer OP-M06 and for the Khadhrawy Mandily cultivar with primer OP-C02. Genetic distance values ranged from 0.868 to 0.125 among studied date palm cultivars. Analysis of genetic relationship showed there were two main groups (A and B), each main group had two subgroups, The first one divided into two subgroups, A1 and A2. A2 subgroup contains the cultivar 'Maktoom', while A1 divided into two subgroups A1a and A1b that contains (9) cultivars (Helaly, Barhee, Khadhrawy.Baghdad, Eusta-Omran, Barbun, Zahdi, Gamal Al-Deen, Mtawag and Khadrawy.Mandily). The main group B divided into two subgroups, B1 subgroup included 'Khastawy' and 'Sultany' cultivars, while B2 subgroup contains 'Ashrasi' and 'Bream' cultivars. According to above results, RAPD markers can be consedered the useful tool to study the genetic relationship among Iraqi date palm cultivars.